The impact of recurrence of primary glomerulonephritis on renal allograft outcome. (15th February 2014) - Moroni, Gabriella; Longhi, Selena; Quaglini, Silvana; Rognoni, Carla; Simonini, Paola; Binda, Valentina; Montagnino, Giuseppe; Messa, Piergiorgio
Abstract Twenty‐yr patient and death‐censored graft survival of 348 kidney transplant recipients with primary glomerulonephritis (GN) and of 696 matched controls were 82.2% in GN patients and 75% in controls (p = 0.037) and 49.5% and 54%, respectively (p = 0.013). GN patients had a higher incidence of graft failure than controls even considering death as a competing risk (p = 0.004). In the GN group, graft survival of deceased and of living donor recipients was similar. At multivariate analysis, GN as primary disease (RR: 1.47), delayed graft function recovery (RR: 2.34), acute rejection (RR: 2.36), and any PRA positivity (RR: 1.01) were predictive of graft loss. GN recurred in 85 of 348 grafts (24.4%), and 43 were lost for recurrence. In non‐recurrent patients, graft survival at 20 yr was significantly better than in recurrent patients (59.4% vs. 24.4%, p = 0.000), but not different from that of controls (59.4 vs. 54%, p = 0.9). At multivariate analysis, young age at transplantation (RR: 0.97), shorter duration of dialysis (RR: 1.05 per each dialysis year), and graft from living donors (RR: 1.668) were independent predictors of recurrence. Patients with primary GN have reduced graft survival in comparison with controls, and this is mainly due to recurrence of original disease. However, the most frequent recurrence in living recipients does not compromise graft survival.